Research and Development Review of Hub Motor Drive Technology for New Energy Vehicles - Zhang, Junhao (Transactions on Environment, Energy and Earth Sciences, 2026)
Under the influence of the dual problems of global energy and environment, countries around the world have actively formulated laws, regulations and related policies to promote the development of electric vehicles. New energy vehicles, with their advantages of energy conservation, environmental protection and high efficiency, have become an important direction for the transformation and upgrading of the future automotive industry. Among them, electric vehicles, as the main type of new energy vehicles, are rapidly popularizing and innovating in technology. The electric drive system is a core component of electric vehicles, and its performance directly affects the power, economy and safety of the entire vehicle. Among the many electric drive schemes, hub motor drive technology has gradually become an important research direction for new energy vehicle drive systems due to its advantages such as compact structure, high transmission efficiency and flexible layout. This paper presents the development of hub motor drive technology and its specific applications, summarizes the current development bottlenecks and countermeasures of hub motors, and finally looks forward to the future development direction of hub motors, providing a reference for the development of hub motor technology in new energy vehicles.